Hubungan Pengetahuan, Sikap dan Perilaku Gizi Seimbang dengan Kejadian Gizi Kurang pada Remaja Putri di SMPN 1 Kota Jambi - Nurkumala, Novita Arum; Chandra, Filius; Gustra Jeki, Andicha; Ariyanto, Ariyanto (3031-8572, 2024)
An individual's knowledge of a balanced diet influences attitudes and behaviours in food choices and nutritional status. Nutritional imbalances can result from inadequate understanding of nutrition. WHO 2016 with the category of undernourishment for girls 8.4% and boys 12.4, Riskesdas 2018 prevalence of nutritional status of adolescents 13- 15 years very thin 2.1% and thin 5.5%. Jambi City Health Office in 2022, the working area of Puskesmas Koni Junior High School level with 444 cases experiencing malnutrition, the purpose of this study was to determine the relationship between knowledge, attitudes and behaviour of balanced diet with the incidence of malnutrition in adolescent girls at SMPN 1 Jambi City in May-June. This type of research is quantitative with a cross-sectional design, data collection by distributing questionnaires and measuring nutritional status. The sample size was 71 people. Data analysis was done using univariate and bivariate analysis using Chi-square test. The results showed a percentage picture of poor knowledge of 19 students (26.8%), moderate attitude of 44 students (62%), adequate behaviour of 34 students (47.9%), poor nutritional status of 16 students (22.5%). There is a relationship between balanced nutrition knowledge and the incidence of malnutrition with a p-value of 0.023, there is no relationship between balanced nutrition attitudes and the incidence of malnutrition with a p-value of 0.059, there is a relationship between balanced nutrition behaviour and the incidence of malnutrition with a p-value of 0.023. It is expected that schools and the Jambi City Health Office can work together to educate adolescents about balanced dietary guidelines.